Minoxidil and nebivolol restore aortic elastic fiber homeostasis in diabetic mice via potassium channel activation - Henry, Auberi; Vanalderwiert, Laetitia; Oszust, Floriane; Wahart, Amandine; Carvajal Berrio, Daniel A.; Brauchle, Eva M.; Schenke-Layland, Katja; Brinckmann, Juergen; Steenbock, Heiko; Debelle, Laurent; Six, Isabelle; Faury, Gilles; et al. (Frontiers in Physiology, 2025)
BackgroundDiabetic patients experience a significant reduction in life expectancy, primarily due to early cardiovascular complications. A key feature is the premature degradation of elastic fibers (EFs), contributing to vascular stiffness.ObjectiveThis study evaluates the capacity of two antihypertensive agents, minoxidil (a KATP channel opener) and nebivolol (a β-blocker with KATP activity), to restore EF homeostasis and arterial elasticity in diabetic mice.MethodsMice are treated with two antihypertensive agents: minoxidil (an ATP-sensitive potassium (KATP) channel opener) or nebivolol (a β-blocker also active on KATP channels). The degree of wear and functionality of EF are assessed after these treatments. We complement this analysis by identifying molecular actors from smooth muscle cell cultures.ResultsOur data show that by applying these antihypertensive agents in cultured vascular smooth muscle cells in vitro and in diabetic mice, we efficiently stimulate elastogenesis and inhibit elastolysis. Therefore, treatments restore functional EFs and limit their degradation. This brings blood pressure values of diseased mice close to normal ones (as in unaffected mice). Elastogenesis pathway stimulation and elastolysis inhibition are induced by the opening of sensitive KATP channels and the regulation of the forkhead box transcription factor (FOXO1).ConclusionMinoxidil and nebivolol restore EF integrity and limit vascular aging in diabetic mice via K+ channel opening and FOXO1 repression. These findings highlight potassium channel–FOXO1 signaling as a therapeutic axis to counteract diabetic vascular complications.